Endogenous and interferon-augmented natural killer cell activity of human peripheral blood mononuclear cells in vitro. Studies of patients with multiple sclerosis, systemic lupus erythematosus or rheumatoid arthritis. - Neighbour, P A (1982)
Peripheral blood mononuclear cells (PBMC) of normal human donors are spontaneously cytotoxic for certain tumour-derived and virus-infected target cells. This so-called natural killing (NK) can be augmented by the action of interferons (IFN) and by IFN-inducers. In this study, we have compared both endogenous and augmented NK activity of normal donors with that of patients suffering from either multiple sclerosis (MS), systemic lupus erythematosus (SLE) or rheumatoid arthritis (RA). Endogenous NK was assayed using an NK susceptible target cell (K562), and augmented NK using a target cell (WI-L2) which is lysed only by NK effector cells that have been pre-stimulated by IFN or IFN-inducers. While NK function appeared normal in RA patients, this study confirms previous reports of defective endogenous NK in many MS and SLE patients. In addition, anomalous IFN-augmented NK was also detected in many patients with these two diseases, indicating that defective NK function cannot always be corrected by IFN treatment in vitro. Analysis of IFN production, endogenous NK and IFN-augmented NK by individual patients with MS or SLE showed the defects in their IFN-NK systems to be highly selective, suggesting that individual components of this system may operate independently.